The Postpartum Maternal and Newborn Microbiomes. Issue 6 (November 2017) - Mutic, Abby D.; Jordan, Sheila; Edwards, Sara M.; Ferranti, Erin P.; Thul, Taylor A.; Yang, Irene
Abstract : Abstract: Biological and environmental changes to maternal and newborn microbiomes in the postnatal period can affect health outcomes for the mother–baby dyad. Postpartum sleep deprivation and unmet dietary needs can alter commensal bacteria within the body and disrupt gut-brain communication. Perineal injury and breast infections also change microbial community composition, potentiating an environment favoring pathogen growth. The gut microbiome refers to the collection of microorganisms working in harmony. Disruptions within the gut microbiome and gut-brain communication may lead to postpartum depression, a potentially devastating sequela. Postnatal newborn changes to the gut and skin microbiome materialize quickly after birth and are profoundly influenced by mode of birth, feeding method, and bathing and skin care practices. During the newborn period, infant microbiomes are highly vulnerable and susceptible to multiple influences. Maternal–newborn nurses have a valuable role in helping mothers and newborns promote healthy microbiomes. Factors that influence the rapidly changing postnatal microbiome of the mother and her newborn, and the role nurses have to positively influence immediate and long-term health outcomes are presented. Abstract : Biological and environmental changes to maternal and newborn microbiomes in the postnatal period can affect health outcomes for mothers and babies. Maternal-baby nurses have a valuable role in helping mothers and newborns promote healthy microbiomes. Factors that influence the rapidly changing postnatal microbiome of the mother and her newborn baby, and the role nurses have to positively influence immediate and long-term health outcomes are presented.